2021
DOI: 10.3390/app11125556
|View full text |Cite
|
Sign up to set email alerts
|

Antenna Design for Microwave and Millimeter Wave Applications: Latest Advances and Prospects

Abstract: Until recently, substantial effort has been devoted to new approaches and attempts to the design of antennas for microwave and millimeter-wave applications [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, due to the current lack of standardization and the multitude of IoT applications, wireless transceivers must operate within a wide range of communication protocols and frequencies in order to guarantee maximal interoperability. Frequencies for IoT can be in the sub-6 GHz spectrum or the mmWave spectrum [ 3 , 4 ], and are predominantly concentrated around the 2.45 GHz industrial, scientific and medical (ISM) band [ 5 ]. Hence, antenna systems are required to exhibit wideband or multiband operation within traditional IoT standards such as WLAN, Bluetooth, WiMAX, or Zigbee, as well as in cellular standards such as 3G, 4G, and future bands for 5G (e.g., the 3.3–3.8 GHz band) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the current lack of standardization and the multitude of IoT applications, wireless transceivers must operate within a wide range of communication protocols and frequencies in order to guarantee maximal interoperability. Frequencies for IoT can be in the sub-6 GHz spectrum or the mmWave spectrum [ 3 , 4 ], and are predominantly concentrated around the 2.45 GHz industrial, scientific and medical (ISM) band [ 5 ]. Hence, antenna systems are required to exhibit wideband or multiband operation within traditional IoT standards such as WLAN, Bluetooth, WiMAX, or Zigbee, as well as in cellular standards such as 3G, 4G, and future bands for 5G (e.g., the 3.3–3.8 GHz band) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In such system configurations, the S-band radar is often employed for the surveillance of targets, whereas the X-band radar is used for the accurate tracking of targets [11,12]. In previous studies, various element types for the S-band and X-band radar systems have been reported, such as patch antennas [13][14][15][16][17][18], dipole antennas [13,14], and Vivaldi antennas [19]. In particular, patch-type antennas with a low profile and reduced radar cross section (RCS) characteristics are considered to be more suitable for military ship MFRs.…”
Section: Introductionmentioning
confidence: 99%